Evaluation of biosurfactant potential from Brevibacillus sp AVN13 for remediation of hydrocarbons and heavy metals - C. Vigneshwaran; V. Sivasubramanian (Carbon: Science and Technology, 2019)
Bioremediation with the help of biosurfactant is one of the promising technologies in treating the hydrocarbon and heavy metal contaminated sites. Biosurfactant was produced naturally by microorganism and hence biodegradable, which is alternative to chemical surfactant for various applications. In this study the biosurfactant producing strain Brevibacillus sp. AVN 13 was used for hydrocarbon and heavy metal remediation. The biosurfactant enhanced biodegradation assay of used engine oil by Brevibacillus sp. AVN 13 was carried out using Erlenmeyer flask experiment and the degradation of hydrocarbon removal rate was analyzed by gas chromatography. The Brevibacillus sp. AVN 13 is having ability to degrade 72 % of hydrocarbon. Then biosurfactant assisted chromium removal process was carried out. The effect of initial chromium concentration, effect of pH, incubation time and concentration of biosurfactant were studied. The removal rate of chromium using biosurfactant was found to be 72.54 % under optimized conditions. Overall this study proved that, biosurfactant from Brevibacillus sp. AVN13 can be effectively used for degradation of oil spilled and heavy metals contaminated sites.